Airway smooth muscle thickness in asthma is related to severity but not duration of asthma - James, A. L; Bai, T. R; Mauad, T; Abramson, M. J; Dolhnikoff, M; McKay, K. O; Maxwell, P. S; Elliot, J. G; Green, F. H (The European respiratory journal, 2009)
Asthma is characterised by an increased airway smooth muscle (ASM) area (ASM area ) within the airway wall. The present study examined the relationship of factors including severity and duration of asthma to ASM area . The perimeter of the basement membrane (PBM) and ASM area were measured on transverse sections of large and small airways from post mortem cases of fatal (n = 107) and nonfatal asthma (n = 37) and from control subjects (n = 69). The thickness of ASM (ASM area /PBM) was compared between asthma groups using multivariate linear regression. When all airways were considered together, ASM area /PBM (in millimetres) was increased in nonfatal (median 0.04; interquartile range 0.013–0.051; p = 0.034) and fatal cases of asthma (0.048; 0.025–0.078; p<0.001) compared with controls (0.036; 0.024–0.042). Compared with cases of nonfatal asthma, ASM area /PBM was greater in cases of fatal asthma in large (p<0.001) and medium (p<0.001), but not small, airways. ASM area /PBM was not related to duration of asthma, age of onset of asthma, sex or smoking. No effect due to study centre, other than that due to sampling strategy, was found. The thickness of the ASM layer is increased in asthma and is related to the severity of asthma but not its duration.